Synthesis and electrochemical characterization of APS/FeCl3-PPy@Co2O3 nanocomposites for supercapacitors - Sagar Kute; Munish Pandey; Manohar Zate (Discover Electronics)
Abstract In this work, we analysed the enhancement of the specific capacitance (Cs) of Co2O3 through the formation of nanocomposites (NCs) with conductive polypyrrole (PPy), presenting a practical approach for developing supercapacitor materials. In this research, PPy@Co2O3 NCs were synthesised using ammonium persulfate (APS) and ferric chloride (FeCl3) as oxidants. They were characterised through structural and electrochemical studies involving UV-Vis, FTIR, BET, XRD, and FE-SEM-EDX analyses. XRD analysis revealed the amorphous nature of PPy and the crystalline nature of Co2O3, while FE-SEM analysis demonstrated the uniform dispersion of Co2O3 within the polymer matrix. Cyclic voltammetry (CV) analysis shows the superior pseudocapacitive performance of NCs, achieving Cs of 118 F/g (Co2O3), 3,244 F/g (APS-PPy@Co2O3), and 438 F/g (FeCl3-PPy@Co2O3) at low scan rates (2–5 mV/s). Combining conductive polymers (APS-PPy, FeCl3-PPy) with Co2O3 improves charge transfer kinetics. This integration reduces diffusion limitations, as shown by the maintained quasi-rectangular CV patterns. This integration effectively mitigates diffusion limitations, as evidenced by the well-maintained quasi-rectangular cyclic voltammetry (CV) patterns and strong rate capabilities (90.7% capacitance retention for APS-PPy@Co2O3 at 20 mV/s). The hybrid charge storage systems that incorporate Faradaic redox processes from Co2+/Co3+ transitions, along with electric double-layer effects, are greatly improved by hierarchical porosity and polymer-induced conductivity, positioning these NCs as strong candidates for high-energy supercapacitors. Graphical abstract